Quercetin enhances human sperm motility in a dose and time dependent manner - Karabulut, Seda; Korkmaz, Oya; Altun, Ceren Erdem; Demiroglu-Zergeroglu, Asuman; Keskin, Ilknur (İstanbul Medipol University secretary@actapharmsci.com, 2020)
The aim of this study was to investigate the effect of quercetin on the motility of ejaculated human spermatozoa in asthenozoospermic cases by using different doses and exposure times. Semen samples of 94 men were incubated with quercetin at different doses and durations. Sperm motility was analysed in each group, and the results were compared. Compared to control, Quercetin improved sperm motility in each molarity and each interval except 1M. Statistically significant increase was assessed at 0.05 M after 1 hours of incubation, and 0.1 M after two hours of incubation (p<0.05). According to our results, it can be suggested that quercetin has a positive effect on sperm motility on a dose and time dependent manner. This study provides evidence for the potential use of quercetin for sperm preparation to be used in assisted reproduction techniques especially in cases of asthenozoospermia. © 2020 Elsevier B.V., All rights reserved.
Keywords: Asthenozoospermia; Motility; Quercetin; Sperm